2006
DOI: 10.1002/glia.20438
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of connexin expression and gap junction communication in astrocytes by the gram‐positive bacterium S. aureus

Abstract: Gap junctions establish direct intercellular conduits between adjacent cells and are formed by the hexameric organization of protein subunits called connexins (Cx). It is unknown whether the proinflammatory milieu that ensues during CNS infection with S. aureus, one of the main etiologic agents of brain abscess in humans, is capable of eliciting regional changes in astrocyte homocellular gap junction communication (GJC) and, by extension, influencing neuron homeostasis at sites distant from the primary focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 75 publications
1
41
1
Order By: Relevance
“…47 Downregulation of gap junction channels results from inflammation and infection. 4851 Several pathways regulating fibroblast growth factor receptors were also significantly enriched (Supplementary Table 3), and are implicated in attachment and replication of certain pathogens. 5255 Pathways related to gap junction channels and fibroblast growth factor receptors may play important roles in mediating respiratory and gut mucosal integrity.…”
Section: Discussionmentioning
confidence: 99%
“…47 Downregulation of gap junction channels results from inflammation and infection. 4851 Several pathways regulating fibroblast growth factor receptors were also significantly enriched (Supplementary Table 3), and are implicated in attachment and replication of certain pathogens. 5255 Pathways related to gap junction channels and fibroblast growth factor receptors may play important roles in mediating respiratory and gut mucosal integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In cultures of primary mouse astrocytes, though, both S. aureus and its peptidoglycan silence gap junction activity, a process that involves the p38 MAPK signaling cascade. At the connexin level, a decrease in mRNA and protein amounts of both Cx30 and Cx43 was observed, whereas Cx26 production became induced [169]. In a recent study, Karpuk and colleagues reported downregulated astrocyte GJIC in brain slices of mice infected with S. aureus.…”
Section: Staphylococcus Aureusmentioning
confidence: 95%
“…Astroglial reactivity is also linked to activation of toll-like TLR2 type receptors (Esen et al ., 2004). Bacterial infection is also reported to down-regulate expression of connexins that form intercellular gap junctional and hence astroglial syncytia, which is regarded as a neuroprotective mechanism, limiting the spread of inflammation (Esen et al ., 2007). Astrogliotic response in the context of bacterial infection has clear defensive capacity: the neurological damage was exacerbated when S. aureus were injected in the brains of mice with the genetic deletion of GFAP (Stenzel et al ., 2004).…”
Section: Infectious Diseases Of the Cnsmentioning
confidence: 99%